Selenoacetalyzation of 4‐Formylpyrazoles in the Presence of Trimethylchlorosilane. Issue 6 (16th September 2013) - Papernaya, Lyubov K.; Shatrova, Alexandra A.; Levanova, Ekaterina P.; Albanov, Alexandr I.; Klyba, Lyudmila V.; Rudyakova, Elena V.; Levkovskaya, Galina G.
ABSTRACT The reaction of 3, 5‐dimethyl‐4‐formylpyrazoles, bearing various substituents at N‐1 atom, with propane‐1, 3‐diselenol and 2‐hydroxypropane‐1, 3‐diselenol in the presence of ТМSCl proceeds without heating to chemoselectively give hitherto unknown 2‐(pyrazol‐4‐yl)‐1, 3‐diselenane hydrochlorides in high yields. The latter are easily transformed to the corresponding free bases—2‐(pyrazol‐4‐yl)‐1, 3‐diselenanes. The 15N chemical shifts of the pyrazole ring in 2‐(pyrazol‐4‐yl)‐1, 3‐diselenanes obtained by 2D HMBC‐gp (15N‐1H) technique are indicative of the N‐2 atom protonation in hydrochlorides.